THE COLONIAL COFFEE COMPULSION MARKETING POLICIES IN KILIMANJARO, TANZANIA - Seimu, Somo M.L. (International Journal of Research -GRANTHAALAYAH, 2016)
This is a historical study that utilises primary evidences from Tanzania National Archives (TNA) to examine the compulsion marketing policies imposed by the Tanzania’s colonial authority among small-scale native coffee producers in the slopes of Mount Kilimanjaro. The policies were provided under Section 36 of the 1932 co-operative legislation. Also, the 1934 Chagga Rule; and the 1937 Native Coffee (Control and Marketing) Ordinance, which became a key and permanent coffee marketing policy in Tanzania that granted the Moshi Native Coffee Board (MNCB) and KNCU monopoly over the native produced coffee.